Genetically encoded fluorescent biosensors for GPCR research - Kim, Hyunbin; Baek, In-Yeop; Seong, Jihye (Frontiers in Cell and Developmental Biology, 2022)
G protein-coupled receptors (GPCRs) regulate a wide range of physiological and pathophysiological cellular processes, thus it is important to understand how GPCRs are activated and function in various cellular contexts. In particular, the activation process of GPCRs is dynamically regulated upon various extracellular stimuli, and emerging evidence suggests the subcellular functions of GPCRs at endosomes and other organelles. Therefore, precise monitoring of the GPCR activation process with high spatiotemporal resolutions is required to investigate the underlying molecular mechanisms of GPCR functions. In this review, we will introduce genetically encoded fluorescent biosensors that can precisely monitor the real-time GPCR activation process in live cells. The process includes the binding of extracellular GPCR ligands, conformational change of GPCR, recruitment of G proteins or β-arrestin, GPCR internalization and trafficking, and the GPCR-related downstream signaling events. We will introduce fluorescent GPCR biosensors based on a variety of strategies such as fluorescent resonance energy transfer (FRET), bioluminescence resonance energy transfer (BRET), circular permuted fluorescent protein (cpFP), and nanobody. We will discuss the pros and cons of these GPCR biosensors as well as their applications in GPCR research.